2021
DOI: 10.1186/s13063-021-05224-6
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nano-curcumin as a nutritional strategy on clinical and inflammatory factors in children with cystic fibrosis: the study protocol for a randomized controlled trial

Abstract: Background Cystic fibrosis (CF) is a genetic disorder, which is caused by the CFTR protein defects. Along with CFTR dysfunction, inflammation plays a key role in the disease outcomes. Inflammation may develop due to the internal dysfunction of the CFTR protein or external factors. Curcumin affects the CFTR protein function primarily as a corrector and potentiator and secondary as an anti-inflammatory and antimicrobial agent. The present study aims to assess the impact of nano-curcumin on clinic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Curcuminoids have received approval from the USA Food and Drug Administration (FDA), and these compounds have good tolerability and safety [26]. Furthermore, they have already been tested with some successes in clinical trials targeting various diseases [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Curcuminoids have received approval from the USA Food and Drug Administration (FDA), and these compounds have good tolerability and safety [26]. Furthermore, they have already been tested with some successes in clinical trials targeting various diseases [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Nano‐curcumin is dosed according to body surface area (child0.25emBSA0.25em()normalm21.730.25em()normalm2 × 80 mg) once daily for 3 months. This study aimed to evaluate the inflammatory state (based on the values of serum Il‐6, IL‐10, and hs‐CRP, stool calprotectin, and neutrophil count of nasopharyngeal swabs) and clinical condition of CF patients (by spirometry, anthropometrics and quality of life) before and after 3 months of curcumin or placebo (Talebi et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, curcumin stimulates CFTR channel activity of both wild type and mutated types (ΔF508‐CFTR and G551D‐CFTR) in a dose‐dependent manner by prolongation of the mean open times (Berger et al, 2005; Cartiera et al, 2010; Zhang, Chen, Wang, Peng, & Cai, 2014). CF patients may also benefit from the antibacterial, antiinflammatory, and antioxidant activities of curcumin (Chaudhary et al, 2019; Karaman, Fırıncı, Arıkan Ayyıldız, & Bahar, 2013; Lee et al, 2010; Talebi et al, 2021). Moreover, a recent systematic review and meta‐analysis found that curcumin improves health‐related quality of life in the adult population (Sadeghian, Rahmani, Jamialahmadi, Johnston, & Sahebkar, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations